Pb andCd Content in Suspended Solid from The Water of tThe Sail River Pekanbaru - Mhd Hari Pratama Rangkuti; Budijono Budijono; M. Hasbi M. Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractMany anthropogenic activities are conducted along the watershed of the Sail River and thus producing pollutant that may enter the water. As the pollutant may contain heavy metals, the metal trace might be found in the water’s suspended solid. A research aims to understand the Pb and Cdcontent in the suspended solid from the river has been conducted in February-March 2019. Sampling were conducted 3 times, once/ 10 days and samples were taken from 3 stations, namely upstream (Station I), middlepart (Station II) and downstream (Station III). Results shown that the average of suspended solid in theupstream was 149 mg/L), in the middle part was 237 mg/L and in the downstream was 114 mg/L. The average of Pb and Cd content in the suspended solids from the upstream was 0.00046 mg/L and 0.0364 mg/L respectively, from the middle part was 0.0030 mg/L and 0.0303 mg/L. While the average of Pb and Cd content in the TSS from the downstream was 0.0024 mg/L and 0.0248 mg/L respectively. Based on data obtained, it can be concluded that the Sail River waters has been contaminated by Pb and Cd.Keywords :heavy metals, river pollution, anthropogenic waste, Plumbum, Cadmium